2006
DOI: 10.1002/cmdc.200500094
|View full text |Cite
|
Sign up to set email alerts
|

Old Molecules for New Receptors: Trp(Nps) Dipeptide Derivatives as Vanilloid TRPV1 Channel Blockers

Abstract: The transient receptor potential vanilloid member 1 (TRPV1), an integrator of multiple pain-producing stimuli, is regarded nowadays as an important biological target for the discovery of novel analgesics. Here, we describe the first experimental evidence for the behavior of an old family of analgesic dipeptides, namely Xaa-Trp(Nps) and Trp(Nps)-Xaa (Xaa=Lys, Arg) derivatives, as potent TRPV1 channel blockers. We also report the synthesis and biological investigation of a series of new conformationally restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…We have previously identified compounds with channel-blocking activity. These antagonists, particularly the N -alkylglycine trimers (peptoids) 5a and 5b (Figure ), block TRPV1 with micromolar efficacy by interacting with the external vestibule of the ionic pore, at a site apparently located outside the membrane electrical field at the pore entry . Although they are active in vivo in animal models of pain, their development was precluded because of unanticipated side effects arising when they were used at submicromolar concentration, namely, release of α-CGRP from nociceptive neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously identified compounds with channel-blocking activity. These antagonists, particularly the N -alkylglycine trimers (peptoids) 5a and 5b (Figure ), block TRPV1 with micromolar efficacy by interacting with the external vestibule of the ionic pore, at a site apparently located outside the membrane electrical field at the pore entry . Although they are active in vivo in animal models of pain, their development was precluded because of unanticipated side effects arising when they were used at submicromolar concentration, namely, release of α-CGRP from nociceptive neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The peptoids 5a and 5b , and other active TRPV1 blockers, ,, share structural features that have been assumed to constitute a basic pharmacophore for TRV1 blocking activity: two aryl moieties and one cationic group. Herein we report the design, synthesis, in vitro screening, and SAR analysis of a new family of TRPV1 antagonists built around a triazine scaffold based on said pharmacophore.…”
Section: Introductionmentioning
confidence: 99%
“…Like ruthenium red [ 5 ], Arg-rich peptides have been described as non-competitive antagonists of TRPV1 receptors, through binding to a site located near the entryway of the aqueous pore [ 6 ]. A few years ago, we found that dipeptide derivatives Xaa-Trp(Nps) and Trp(Nps)-Xaa (Xaa=Lys, Arg, Nps = 2- o -nitrophenylsulfenyl), first described as analgesic dipeptides of unknown mechanism of action [ 7 , 8 ], inhibited the activation of TRPV1 in the micromolar range, and also acted as NMDA channel blockers, although with lower potency [ 9 ]. In view of their structural analogy with the Arg-rich peptides, it was hypothesized that these Nps-containing dipeptides could interact with the vanilloid receptor through the pore entrance.…”
Section: Introductionmentioning
confidence: 99%